DATA EXPLORATION OF STUDENT PERFORMANCE UNDER THE MERDEKA CURRICULUM: A CASE STUDY AT MAN 1 PANDEGLANG - Aat Royhatudin; Ahmad Hidayat; Ujon Sujono; Eti Fatiroh; Saepudin Bahri (Staisman Press, 2026)
The implementation of the Merdeka Curriculum (Kurikulum Merdeka) in Indonesian madrasahs represents a significant pedagogical shift, yet empirical evidence on its relationship with student performance remains limited. This study conducts a data exploration of student performance under the Merdeka Curriculum at MAN 1 Pandeglang, aiming to identify patterns, trends, and key determinants of academic outcomes. Using a quantitative exploratory design, we analyzed secondary data from 180 tenth-grade students across three semesters, including report card grades, formative assessment scores, attendance records, and participation in project-based learning (PjBL) activities. Descriptive statistics, trend analysis, and correlation tests were employed to explore the data. The findings reveal three main patterns: first, project-based learning participation shows a moderate positive correlation with final semester grades (r = 0.52); second, consistent attendance above 90% is associated with higher performance stability across all subjects; and third, students demonstrate improved outcomes in literacy and numeracy assessments compared to pre-curriculum baseline data. However, wide variability in performance across different project themes suggests uneven implementation fidelity. Compared to previous studies on competency-based curricula, these results highlight the unique role of madrasah cultural contexts in moderating curriculum effectiveness. This study contributes baseline empirical data from an understudied population and offers practical insights for curriculum adaptation at MAN 1 Pandeglang, with broader implications for madrasahs nationwide adopting the Merdeka Curriculum.